A Case Series of Hyperglycemic Hyperosmolar State During the Global COVID-19 Pandemic - Hoag, Benjamin Donald (J Endocr Soc, 2021)
Hyperglycemic hyperosmolar state (HHS) is rare in pediatrics, particularly in patients with antibody positive diabetes mellitus (DM). Recent literature has implicated COVID-19 in the reported increase in new-onset DM cases, as well as mixed diabetic ketoacidosis (DKA) and HHS cases, however a rise in HHS cases alone has not been well reported [1,2]. We noted an anecdotal increase in the frequency of HHS cases in our pediatric tertiary care center following the onset of the global COVID-19 pandemic. To investigate further, a retrospective chart review evaluating all patients with DM admitted in the first 6 months of 2019 and the first 6 months of 2020 was conducted. A diagnosis of HHS was defined as a blood glucose over 600 mg/dL with a serum osmolality (calculated or measured) greater than 320 mOsm/kg on initial laboratory evaluation. Patients with DKA, defined as a serum bicarbonate level less than 16 mmol/L with evidence of significant ketosis (serum ketones greater than 3 mmol/L), were excluded from the study. During the first 6 months of 2019, 1 patient met inclusion criteria. However, the diagnosis of HHS was complicated by a concurrent diagnosis of diabetes insipidus, which may have contributed to the hyperosmolar state, and a nonketotic lactic acidosis. Five HHS cases were noted in the first 6 months of 2020, 4 of which occurred in May and June. For the 2020 HHS cohort, the average patient age ± SD was 12 ± 3.34 years. The mean ± SD laboratory values included bicarbonate 18.2 ± 1.64 mmol/L, serum blood glucose 776.8 ± 30.75 mg/dL, calculated serum osmolality 328 ± 4.18 mOsm/kg, and HgA1C 12.72 ± 1.16%. All 5 patients in the 2020 cohort had new-onset DM, with 4 of the 5 patients having at least 1 positive DM antibody (GAD antibodies were positive in 3, ICA/IA-2 antibodies in 2, and Zinc Transporter 8 antibodies in 1). No patients displayed COVID-19 symptoms, and only 1 patient was tested for COVID-19 by PCR, which returned negative. However, SARS-CoV2 antibody testing was not available, and it is unknown if these patients had prior COVID-19 illness. In conclusion, we noted an increased incidence of HHS at our hospital, particularly among new-onset, antibody positive DM patients during the initial months of the COVID-19 pandemic. Further study and investigation are needed to determine the cause of this increased local incidence, and if infectious, social, or economic influences related to the COVID-19 pandemic contributed. References: [1] Chan, K.H., et al., Clinical characteristics and outcome in patients with combined diabetic ketoacidosis and hyperosmolar hyperglycemic state associated with COVID-19: A retrospective, hospital-based observational case series. Diabetes Res Clin Pract, 2020. 166: p. 108279. [2] Unsworth, R., et al., New-Onset Type 1 Diabetes in Children During COVID-19: Multicenter Regional Findings in the U.K. Diabetes Care, 2020.